Investigating The Resources Affecting Japanese Business Affiliates’ Cross-Border Knowledge Transfer In Northern Malaysia - Wong, Mei Foong (2019)
Japanese companies are well-known in Malaysia because many of these multi national corporations (MNCs) expanded their international presence in Malaysia in multisearch of a more conducive business environment since the early 1960s.